Effect of Processing on p-Hydroxybenzoic Acid Content of Cereals-A Review - Boz, Hüseyin (Food Science and Engineering, 2026)
Cereals hold an important place in human nutrition due to their high content of numerous bioactive compounds, primarily phenolic acids. This review aims to evaluate the presence and distribution of p-Hydroxybenzoic Acid (p-HBA) in cereals and pseudo-cereals, and the effects of different food processing methods on p-hydroxybenzoic acid content, in light of the literature findings. Current studies indicate that p-hydroxybenzoic acid is predominantly found in the bran, aleurone layer, and embryo of cereals, and its content decreases significantly with refining processes. Biological processes such as germination and fermentation lead to significant increases in p-HBA content by releasing phenolic acids present in bound form in the grain matrix. This effect is reported to be further enhanced, and multi-fold increases are observed, particularly when supported by enzymatic treatments. The effects of heat treatments on p-hydroxybenzoic acid vary depending on the method and conditions applied. Long-term high-temperature treatments, such as baking, can cause p-hydroxybenzoic acid losses, while short-term treatments, such as microwaves, can promote p-hydroxybenzoic acid release by disrupting cell wall structures. In conclusion, p-hydroxybenzoic acid appears to be a phenolic acid sensitive to grain processing methods, and its content can be increased with appropriate processing strategies. These findings suggest that the development of p-hydroxybenzoic acid-enriched whole grain and pseudo-cereal products offers a significant approach to high-nutritional-quality and health-focused foods.